Modulating Effect of Vitamin D on iNOS, PCNA and a-SMA Expression Against Diclofenac Sodium Induced Gastric Injury in Rats - Sahar Youssef (The Prodia Education and Research Institute (PERI), 2020)
BACKGROUND: Diclofenac sodium is a nonsteroidal anti-inflammatory prescription, widely used in the management of many inflammatory diseases but the side effects limiting its clinical use. The present work was carried out to detect the ameliorative effect of vitamin D against diclofenac sodium induced gastric injury in adult male albino rats.METHODS: Forty adult male Wistar albino rats were classified into four groups: G-I received no treatment (control group), G-II orally received 500 IU/kg of vitamin D daily, G-III intraperitoneally received 3 mg/kg of diclofenac sodium daily, and G-IV received both 500 IU/kg of vitamin D and 3 mg/kg of diclofenac sodium daily for 14 days. Specimens from rats' stomach were processed for light microscopy. Immunohistochemical examination was carried out to detect inducible nitric oxide synthase (iNOS), proliferating cell nuclear antigen (PCNA), and alpha smooth muscle actin (α-SMA). The morphometric results were analyzed statistically.RESULTS: Gastric sections of G-III displayed inflammatory cellular infiltrations and dilated congested blood vessels. Some of the gastric gland cells showed cytoplasmic vacuolation, dilated gastric pits, and cystic dilatation. There was a significant increased Masson's trichrome stain and a significant decrease in PAS. The mean area percentage of iNOS and α-SMA expression showed a statistically significant increase. The PCNA positive cells were significantly decreased in the isthmus and neck region compared with the control. While in contrast, G-IV prevented the gastric injury by increasing PAS and PCNA but decreasing Masson's trichrome stain, iNOS and α-SMA expression.CONCLUSION: Vitamin D administration prevented the structural alterations of the gastric rat induced by diclofenac sodium.KEYWORDS: diclofenac sodium, α-SMA, iNOS, PCNA, vitamin D